New Trends in Structural Engineering - Ehsan Noroozinejad Farsangi; Hakan Yalciner (IntechOpen, 2018)
The book presents a collection of articles on novel approaches to problems of current interest in structural engineering by academicians, researchers, and practicing structural engineers from all over the world. The book is divided into five chapters and encompasses multidisciplinary areas within structural engineering, such as structural dynamics and impact loading, structural mechanics, finite element modeling, structural vibration control, and the application of advanced composite materials. New Trends in Structural Engineering is a useful reference material for the structural engineering fraternity, including undergraduate and postgraduate students, academicians, researchers, and practicing engineers.
English
Keywords: Engineering; Physical Sciences; Engineering and Technology; Structural Engineering; Civil Engineering